2005
DOI: 10.1111/j.1529-8817.2005.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH STIMULATION OF ALEXANDRIUM TAMARENSE (DINOPHYCEAE) BY HUMIC SUBSTANCES FROM THE MANICOUAGAN RIVER (EASTERN CANADA)1

Abstract: In the St. Lawrence Estuary, annual recurrent blooms of the toxic dinoflagellate Alexandrium tamarense L. Balech are associated with brackish waters. Riverine inputs are suspected to favor bloom development by increasing water column stability and/or by providing growth stimulants such as humic substances (HS). A 17-day culture experiment was conducted to evaluate the importance of HS as growth factors for A. tamarense. Nonaxenic cultures were exposed to four HS extracts from three different sources: humic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…More recently, the uptake of laboratory-produced 15 N-labeled humic compounds by the >0.7 µm size fraction has been observed in both riverine and coastal ecosystems (Bronk et al, unpublished data), humic substances have been implicated as a potential source of C and N to the toxic dinoflagellate Alexandrium catenella (Doblin et al, 2000), and growth of another toxic dinoflagellate Alexandrium tamarense was shown to increase when exposed to humic substances (Gagnon et al, 2005). Uptake of humic-N into phytoplankton biomass was also measured directly using 15 N-labeled humic substances produced in the laboratory (See and Bronk, 2005).…”
Section: The Special Case Of Humicsmentioning
confidence: 99%
“…More recently, the uptake of laboratory-produced 15 N-labeled humic compounds by the >0.7 µm size fraction has been observed in both riverine and coastal ecosystems (Bronk et al, unpublished data), humic substances have been implicated as a potential source of C and N to the toxic dinoflagellate Alexandrium catenella (Doblin et al, 2000), and growth of another toxic dinoflagellate Alexandrium tamarense was shown to increase when exposed to humic substances (Gagnon et al, 2005). Uptake of humic-N into phytoplankton biomass was also measured directly using 15 N-labeled humic substances produced in the laboratory (See and Bronk, 2005).…”
Section: The Special Case Of Humicsmentioning
confidence: 99%
“…It is known, that the growth rate of Gonyostomum is supported by fulvic acids (Rengefors et al, 2008), which may explain the continuous increase of adult cell numbers in our experimental peat tanks, in contrast to controls and glucose treatments. Humic substances have been also shown to positively affect the growth rate of some dinoflagellates (Prakash & Rashid, 1968;Doblin et al, 1999;Gagnon et al, 2005); however, there is no single study concerning the impact of humic substances on any algal cyst germination.…”
Section: Discussionmentioning
confidence: 99%
“…Such a change in DOC composition could be an important factor in controlling the competition between phytoplanktonic species, in particular in the ability of A. minutum to reach very high concentrations (10 6 cells L À1 ) to the detriment of other species (Chapelle et al, 2010;and references therein). Several studies have revealed that HS additions can positively affect the growth rate and biomass production of dinoflagellates (Carlsson et al, 1998;Doblin et al, 1999;Gagnon et al, 2005;Heil, 2005). The concomitant increase in discharge of HS into Swedish rivers and the natural incidence of dinoflagellate blooms over a decade has also been reported (Granéli and Moreira, 1990).…”
Section: Hs Behaviour Along the Salinity Gradientmentioning
confidence: 99%
“…Terrestrial humic material, deriving mainly from decay of lignin-containing plants, is thought to account for most of the humic substances present in these systems (Ehrhardt, 1984;Tremblay and Gagné, 2009). Among various important characteristics, HS have been shown to enhance solubility of organic pollutants and pesticides (Chiou et al, 1986;Tanaka et al, 1997;Blasioli et al, 2008); stimulate growth rate and biomass production of dinoflagellates (Doblin et al, 1999;Gagnon et al, 2005); and provide an energy source for a variety of estuarine sedimentary microorganisms under both aerobic and anaerobic conditions (Alberts and Filip, 1994;Rocker et al, 2012). Similar to DOM, the behaviour of HS during transport to the marine environment is still very unclear (Dittmar and Kattner, 2003).…”
Section: Introductionmentioning
confidence: 99%